An overview of encapsulation of active compounds used in food products by drying technology. (1st March 2016) - Ray, Sohini; Raychaudhuri, Utpal; Chakraborty, Runu
Abstract: Drying is an important process parameter for preservation of food components and it is widely applicable in food sectors. Nowadays, encapsulation by drying technology is of growing interest to provide many useful effects in food industry. Encapsulation of several drying techniques (spray drying, freeze drying, and fluidized bed coating) is a challenge to incorporate food component, antioxidant, colorant, cells and enzymes in powder form in food products. By drying, encapsulation achieves excellent properties of protection, stabilization, solubility and controlled release of the bioactive compounds. There are many reasons to apply encapsulation technology by drying, so recent developments of encapsulation are discussed in this review. Controlled release of food component at the right place at right time is a key functionality that can be provided by encapsulation. Drying improves effectiveness of food additives, broadens the application range of food ingredients, enhances shelf life of the food and lowers cost of the food products.